STRATEGI GEREJA DALAM MENINGKATKAN PEDAGOGIS MISI TERHADAP ANAK SEKOLAH MINGGU - Riska Bungin; Sarmiati Bangnga Bua (ADISAM PUBLISHER, 2026)
This article discusses the church's strategy in improving missionary pedagogy for Sunday School children, focusing on the importance of collaboration between the church and family in faith and mission education. A theological understanding of Missio Dei is the basis for forming children's missionary character, while a creative and experience-based pedagogical approach is expected to increase children's involvement in the church's mission. The challenges of globalization and digitalization, including the flow of information that is not always in accordance with faith values, are important factors that influence the effectiveness of teaching. The church, as a spiritual formation community, plays a role in equipping families through family-based mission training and activities. The synergy between the church and the family is expected to be able to form a young generation who not only know the Christian faith, but also live as active mission actors in the world. This article suggests the development of a curriculum and teaching methods that are contextual, interactive, and applicable